2016
DOI: 10.12816/0033485
|View full text |Cite
|
Sign up to set email alerts
|

Vernal Keratoconjunctivitis and Severe Keratoconus Associated with Autoimmune Polyglandular Syndrome Type II ( APS-2 ) : A Case Report

Abstract: Vernal keratoconjunctivitis (VKC) is a bilateral, usually seasonally recurrent inflammation of the conjunctiva. Even though it is an uncommon type of allergic eye disease but in some cases it can cause severe damage to the ocular surface, leading to keratoconus (KC) and vision loss. We report a rare case of vernal keratoconjunctivitis and keratoconus diagnosed since childhood and then was diagnosed years later with Addison's disease and subclinical hypothyroidism. Even though the association between VKC and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The association between autoimmune diseases and KC has been suggested based on retrospective studies and case reports [ 20 24 ]. A recent study showed a prevalence of thyroid gland dysfunction of 13.6% in patients with KC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between autoimmune diseases and KC has been suggested based on retrospective studies and case reports [ 20 24 ]. A recent study showed a prevalence of thyroid gland dysfunction of 13.6% in patients with KC [ 25 ].…”
Section: Introductionmentioning
confidence: 99%